Stress in wild greater rhea populations: effects of agricultural activities on fecal glucocorticoid metabolite levels - Leche, A. (2014)
Fil: Leche, A. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Diversidad y Ecología Animal; Argentina.